Interest Rate and Inflation Control in Egypt: Evaluating policy efficiency (1976-2023) - Abouzeid, Fatma (AUC Knowledge Fountain, 2026)
Inflation has been a persistent problem in Egypt peaking with unprecedented levels throughout the past decades affecting economic stability and living standards in the country. Controlling inflation through interest rate has been a major tool adopted by the monetary authorities in Egypt with no real satisfactory outcome with respect to inflation levels. This links to a theoretical debate in economic literate on the relationship between interest rate and inflation which represents a major controversy in the field. The study examines this controversy in the case of Egypt to reach a conclusion on the actual relationship between these two central economic indicators within the economic framework in Egypt between 1976 and 2023. The study applies a quantitative approach to empirically examine the relationship between the two variables and the efficiency of changing interest rate to control inflation accounting for other related variables namely money supply, exchange rate, gross domestic product. The study adopts the Autoregressive Distributed Lag (ARDL) and uses several checking tests that provide insightful results and support robustness of the model including cointegration test, serial correlation test, normality test, heteroskedasticity test and CUSUM stability test. Differentiating between nominal and real interest rates, it was found that while increasing interest rate leads to a decrease of 0.905 in inflation rate in the long run, increasing nominal interest rate increases inflation with 1.275 in the long run. This has significant policy implications with respect to real economic indicators that can be used to control inflation.